ANALISIS PERDA NO 13 TAHUN 2003 TENTANG APBD SEBAGAI FAKTOR KRIMINOGEN DALAM TINDAK PIDANA KORUPSI OLEH ANGGOTA DPRD SURAKARTA PERIODE 1999 - 2004 - Ismunarno, Ismunarno (Faculty of Law, Universitas Sebelas Maret, 2012)
AbstractThis study aims to determine whether Perda could be kriminogen facts in a corruption and identify the location of the fault of the parties involved in relation to the regulation if it is based on Law no. 31 of 1999 Jo Law. 20 of 2001 on the eradication of corruption. This study is a descriptive normative nature. This research included literature research therefore examines only secondary data. Based on the research result that Perda No. 13 of 2003 on budget is an amendment to the budget previously provided for in Regulation No. 1 of 2003. Changes made include sector budget: Education, Culture, Belief in God Almighty, Youth and Sports (budget increase), Population and Family Welfare (Budget derived), Health (Budget falls), Housing and settlement lowered (Budget falls), Recurrent Parliament (Budget rises), Welfare (Budget falls), Travel allowance legislators (budget increase), Shopping goods (Articles ride). From the description above indicates that the changes are more likely to benefit / for the personal benefit of the members of Parliament, because of budget increases are related to the interests of members of parliament. Perda No 13 out 2003 on the budget that alter the law No. 1 Year 2003 there Kriminogen factor which is the act of corruption in particular violates Article 2 (1) and Article 3 of Law no. Jo 31 of 1999 Law No. 20 of 2001 on corruption because of errors in the process of changing the budget and the lack of legal basis as well as budget expenditures in the determination of certain sectors as described. From this research are expected to provide input on efforts that can be done to minimize corruption, especially by the executive and legislative branches in the region rose sharply as the enactment of local autonomy.